2017
DOI: 10.1001/jamaoto.2016.4735
|View full text |Cite
|
Sign up to set email alerts
|

Neurologic Evaluation in Children With Laryngeal Cleft

Abstract: A substantial proportion of patients with laryngeal cleft have coexistent neuromuscular dysfunction as a likely contributing factor to dysphagia and aspiration. Collaboration with a neurologist and appropriate neuroimaging may provide diagnostic and prognostic information in this subset of patients. At times, imaging will identify critical congenital malformations that require surgical treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
12
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 20 publications
3
12
1
Order By: Relevance
“…It has to be noted that yet failure to thrive was present in seven of the children despite jejunostomy, high‐calorie nutrition, and absence of intestinal problems. A recent study found coexisting neuromuscular dysfunction or dyscoordination in patients with LTECs contributing to dysphagia and aspiration 28 . This is in accordance with our findings reporting normal neurological development in less than half of the patients.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…It has to be noted that yet failure to thrive was present in seven of the children despite jejunostomy, high‐calorie nutrition, and absence of intestinal problems. A recent study found coexisting neuromuscular dysfunction or dyscoordination in patients with LTECs contributing to dysphagia and aspiration 28 . This is in accordance with our findings reporting normal neurological development in less than half of the patients.…”
Section: Discussionsupporting
confidence: 93%
“…The tracheomalacia remains significant after surgery due to the abnormal tracheal wall structure and often-occurring redundancy of the surgically created posterior tracheal wall. 14 28 This is in accordance with our findings reporting normal neurological development in less than half of the patients. Finally, congenital heart defects were reported more often in our cohort.…”
Section: Clinical Course and Outcomesupporting
confidence: 93%
“…A selection bias was likely present for those patients undergoing MDL without VFSS because OSA was likely the main indication for the MDL instead of dysphagia. Although patients with neurological disorders or Trisomy 21 have been found to have higher rates of pharyngeal dysphagia that those without these comorbidities, our cohort did not show any significant clustering for any one group . However, the numbers of patients with these comorbidities were small and could have affected the ability to detect a difference.…”
Section: Discussioncontrasting
confidence: 57%
“…Airway disorders, such as vallecular cyst, laryngomalacia, vocal fold immobility, and laryngotracheoesophageal cleft, can be diagnosed. [24][25][26][27] Tracheoscopy can diagnose tracheomalacia, tracheal stenosis, and tracheoesophageal fistula. 29 Bronchoscopymayassessforbronchomalacia,bronchiectasis,andevidence of chronic aspiration and pneumonias.…”
Section: Endoscopic Evaluationsmentioning
confidence: 99%